Economic development, population and civil war: a Bayesian changepoint model. Issue 1 (1st April 2021) - Luo, Shali; Choi, Seung-Whan
Abstract : Purpose: This study proposes a Bayesian approach to analyze structural breaks and examines whether structural changes have occurred, at the onset of civil war, with respect to economic development and population during the period from 1945 to 1999. Design/methodology/approach: In the Bayesian logit regression changepoint model, parameters of covariates are allowed to shift individually, regime transitions can move back and forth, and the model is applicable to cross-sectional, time-series data. Findings: Contrary to popular belief that the causal process of civil war changed with the end of the Cold War, the empirical analysis shows that the regression relationships between civil war and economic development, as well as between civil war and population, remain quite stable during the study period. Originality/value: This is the first to develop a Bayesian logit regression changepoint model and to apply it to studies of economic development and civil war.